Integrated automatic industrial waste water reuse of reclaimed water device - MAO SHUAILONG; DING BENXIU (2016)
The utility model discloses an integrated automatic industrial waste water reuse of reclaimed water device, include: pre treatment device for filter suspended particles and chlorine residue in the waste water, the milipore filter, with pre treatment device links to each other for filter in the waste water impurity such as particle suspended solid that the particle diameter is lighter than 0.1 mu m, colloid, bacterium, anti - flushing device, it is regularly right to be used for the milipore filter carries out the back flush, detaches the pollutant of epimembranal face, resumes the membrane flux, reverse osmosis membrane, with the milipore filter links to each other for play water to the milipore filter carries out desalination. The utility model discloses device integration ization, automatic adopts membrane processing technique, and treated water water good quality is good, and messenger's water resource can recycle to satisfy more, higher water demand, the range of application is extensive. 本实用新型揭示了种集成自动化的工